2017
DOI: 10.4236/ojped.2017.73020
|View full text |Cite
|
Sign up to set email alerts
|

Etiological and Evolutionary Profile of the Child’s Pericarditis in Tropical Environments

Abstract: Background: Liquid pericarditis is a frequent cause of hospitalization in developing countries. Objective: of this study was to describe the etiological and evolutionary aspects of fluid pericarditis in pediatric cardiology at ICA. Methods: This was a retrospective study of 42 cases of fluid pericarditis diagnosed among 202 children hospitalized over a five-year period (1 st January 2009 to 31 st December 2014). All patients with pericardial effusion were included in the study. Results: Prevalence was estimate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
2

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 24 publications
0
1
0
2
Order By: Relevance
“…6 El diagnóstico es clínico y eléctrico, basado en al menos dos de cuatro criterios: dolor torácico, frote pericárdico, anomalías electrocardiográfi cas com-patibles (elevación difusa del segmento ST con o sin onda T de corta duración, desnivel del segmento PR) o derrame pericárdico en ecocardiograma. 1,7,8 En países de bajos ingresos, donde entidades infecciosas como el virus de la inmunodefi ciencia humana o la tuberculosis son endémicas (por ejemplo, en poblaciones de la India y África), la principal causa de pericarditis es infecciosa. 8,9 En países de altos ingresos, la causa suele ser benigna y son más frecuentes las formas idiopáticas e infecciosas.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…6 El diagnóstico es clínico y eléctrico, basado en al menos dos de cuatro criterios: dolor torácico, frote pericárdico, anomalías electrocardiográfi cas com-patibles (elevación difusa del segmento ST con o sin onda T de corta duración, desnivel del segmento PR) o derrame pericárdico en ecocardiograma. 1,7,8 En países de bajos ingresos, donde entidades infecciosas como el virus de la inmunodefi ciencia humana o la tuberculosis son endémicas (por ejemplo, en poblaciones de la India y África), la principal causa de pericarditis es infecciosa. 8,9 En países de altos ingresos, la causa suele ser benigna y son más frecuentes las formas idiopáticas e infecciosas.…”
Section: Discussionunclassified
“…1,7,8 En países de bajos ingresos, donde entidades infecciosas como el virus de la inmunodefi ciencia humana o la tuberculosis son endémicas (por ejemplo, en poblaciones de la India y África), la principal causa de pericarditis es infecciosa. 8,9 En países de altos ingresos, la causa suele ser benigna y son más frecuentes las formas idiopáticas e infecciosas. 1 El tratamiento farmacológico de primera línea en la pericarditis aguda son los antiinfl amatorios no esteroideos (ácido acetilsalicílico, indometacina o ibuprofeno) durante dos o tres semanas.…”
Section: Discussionunclassified
“…Tougouma et al [3] in Burkina Faso and Ngouala et al [4] in Senegal reported hospital prevalence in children of 4.3‰ and 6‰, respectively, with predominantly congenital forms. In Côte d'Ivoire, heart disease has been the subject of very few studies in children [5] [6] [7]. All these studies were conducted in Abidjan so that the national prevalence of childhood heart disease is unknown.…”
Section: Introductionmentioning
confidence: 99%